Edukasi tentang Monitoring Anestesi Aman di Fasilitas Kesehatan - Bayu Despriyanto Pratama; Galih Pria Pambayun (Lembaga Pengembangan Kinerja Dosen, 2024)
Safe anesthesia monitoring is a crucial aspect of medical procedures to ensure patient safety during anesthesia administration. A lack of knowledge and skills among healthcare professionals in anesthesia monitoring can increase the risk of complications and undesirable side effects. The educational program on safe anesthesia monitoring in healthcare facilities aims to enhance medical professionals' knowledge, skills, and awareness in implementing appropriate monitoring standards. This study employs a descriptive approach to evaluate the effectiveness of the educational program through interactive training methods, clinical simulations, and competency-based assessments. The results indicate that the provided education significantly improves participants' understanding of safe anesthesia monitoring principles and reduces errors in clinical practice. Therefore, education on safe anesthesia monitoring should be an integral part of medical training to enhance healthcare quality and patient safety..